Nonoperative Treatment of Ulnar Carpometacarpal Fracture–Dislocations - Jiménez, Isidro; Sánchez-Hernández, Juan; Kiimetoglou, Dimosthenis (Journal of Wrist Surgery, 2020)
Background Ulnar carpometacarpal (CMC) joint dislocations and fracture–dislocations are uncommon injuries that are often overlooked. Most authors advocate surgical stabilization in order to prevent a secondary dislocation assuming that these injuries are inherently unstable.Case Description This is a series of eight ulnar CMC joint dislocations and fracture–dislocations treated by closed reduction and splint immobilization after assessing the joint stability. Mean follow-up was 30.2 months, and minimum follow-up was 12 months. Satisfactory results were obtained in range of motion, grip strength, pain, DASH (Disabilities of the Arm, Shoulder and Hand) questionnaire, and time to return to working activities. In the same period, the closed reduction and cast failed two (20%) cases that were referred for surgery.Literature Review There is little published literature on the nonoperative treatment of these injuries. Most of them are isolated case reports, whereas the largest series reports four cases. All of them have reported satisfactory results.Clinical Relevance Based on our results, we believe that if the diagnosis of an ulnar CMC joint dislocation or fracture–dislocation is early accomplished and a concentric and stable reduction is initially achieved, the nonoperative treatment may be a successful option to take into account but requiring a close follow-up for the first week.
Keywords: carpal; dislocation; fracture; metacarpal; ulnar